Incremental Prognostic Value of Conventional Echocardiography in Patients with Acutely Decompensated Heart Failure - Soares,Fabio Luis de Jesus (2017)
Abstract Background: Acutely decompensated heart failure (ADHF) presents high morbidity and mortality in spite of therapeutic advance. Identifying factors of worst prognosis is important to improve assistance during the hospital phase and follow-up after discharge. The use of echocardiography for diagnosis and therapeutic guidance has been of great utility in clinical practice. However, it is not clear if it could also be useful for risk determination and classification in patients with ADHF and if it is capable of adding prognostic value to a clinical score (OPTIMIZE-HF). Objective: To identify the echocardiographic variables with independent prognostic value and to test their incremental value to a clinical score. Methods: Prospective cohort of patients consecutively admitted between January 2013 and January 2015, with diagnosis of acutely decompensated heart failure, followed up to 60 days after discharge. Inclusion criteria were raised plasma level of NT-proBNP (> 450 pg/ml for patients under 50 years of age or NT-proBNP > 900 pg/ml for patients over 50 years of age) and at least one of the signs and symptoms: dyspnea at rest, low cardiac output or signs of right-sided HF. The primary outcome was the composite of death and readmission for decompensated heart failure within 60 days. Results: Study participants included 110 individuals with average age of 68 ± 16 years, 55% male. The most frequent causes of decompensation (51%) were transgression of the diet and irregular use of medication. Reduced ejection fraction (<40%) was present in 47% of cases, and the NT-proBNP median was 3947 (IIQ = 2370 to 7000). In multivariate analysis, out of the 16 echocardiographic variables studied, only pulmonary artery systolic pressure remained as an independent predictor, but it did not significantly increment the C-statistic of the OPTMIZE-HF score. Conclusion: The addition of echocardiographic variables to the OPTIMIZE-HF score, with the exception of left ventricular ejection fraction, did not improve its prognostic accuracy concerning cardiovascular events (death or readmission) within 60 days